Properties of Logs
Logarithm product rule
logb(x * y) = logb(x) + logb(y) Logarithm quotient rule logb(x / y) = logb(x) - logb(y) Logarithm power rule logb(xy) = y * logb(x)
The log is the inverse of the exponential function so 43 =
is the inverse of log4 64 = Product Rule of Logs log2 4 + log2 8 = 5 We can also solve this by multiplying the bases together and get log2 32 = 5 When we add together logs that have the same bases we can combine them by multiplying the numbers we are taking the log of. logb (x * y) = logb x + logb y log6 12 + log6 18 = log6 216 = 3 log2 32 = log2 4 + log2 8 = 2 + 3 + 5 The Power Rule of Logs If we have log7 x3 = log7 (x * x * x) = log7 x + log7 (x * x) = log7 x + log7 x + log7 x = 3 (log7 x) - so when we take the log of something that has an exponent we can move the exponent as a multiplier to the front of the expression. log2 64 = log2 (4 * 4 * 4) log2 (43) = 3 (log2 4) = 3 * 2 = 6 logbxn = n logb x - - - - - - - - - - - - - - - - - - - - - - 42x = 6 log (42x) = log(6) 2x log(4) = log(6) 2x = (log(6)/log(4) x = log(6)/log(4)/2 - - - - - - - - - - - - - - - - - - - - - - 2x+3 = 54 log (2x+3) = log(54) (x+3) log(2) = log(54) x log(2) + 3 log(2) = log(54) x log(2) = log(54) - 3 log(2) x = (log(54) - 3 log(2)) / log(2) x = 2.7548 Exponentail Rule (Inverse of the log) log4 (x -1 ) = 3 4log4(x-1) = 43 x-1 = 64 x = 65 log(x+2) = 4 10log(x+2) = 104 x + 2 = 10000 x = 9998 Logarithm Quotient Rule log(30x) - log(6) = 4 log(30x/6) = 4 log(5x) = 4 10log(5x) = 104 // exponental rule 5x = 10000 x = 2000 - - - - - - - - - - - - - - - - - - - - - - log5 25 - log5 5 = log5 (25/5) = log5 (5) = 1 |